Status of Waterbirds of Ambasamudram Tank, Tirunelveli, Tamilnadu - Ramarajan, Sekar; Kumar, Pandian; Darwin Paul Edison, S. (Indian Forester, 2015)
Ambasamudram irrigation tanks have socio-economic and cultural significance, very little is known of their ecological importance. These tanks have the potential to harbor good populations of resident and wintering waterbirds but no studies have been done to confirm this. A survey was carried out in Ambasamudram tanks from November 2013 to January 2014. A total of 32 waterbird species were recorded. Ambasamudram tanks had good population of birds and this site along with associated wetlands is important for the long term conservation of waterbirds in the region.